2021
DOI: 10.1002/smll.202103933
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Photoelectrode Photoassisted Fe–Air Battery: The Photo‐Electrocatalysis Mechanism Accounting for the Improved Oxygen Evolution Reaction and Oxygen Reduction Reaction of Air Electrodes

Abstract: Seeking advanced energy conversion devices, which are sustainable as well as environment friendly, is extremely challenging in our modern society. [3,4] In this regard, the metal-air battery is among the alternative costeffective battery technologies with high energy density, environmentally friendly, and which is composed of an air electrode and a metal electrode, generating electricity through the redox reaction. [5] Among the various metal-air batteries, Li-air and Zn-air batteries have received the most ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 56 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…CuO photoelectrodes were employed for separated photoelectrodes. [70] This photo-assisted FeÀ O 2 battery achieved a low charging voltage of 0.64 V and a high discharging voltage of 1.38 V at 0.1 mA cm À 2 under illumination. As presented above, the photo-assisted strategies were viable to promote performances in current metal air battery systems.…”
Section: Chemistry-a European Journalmentioning
confidence: 89%
See 1 more Smart Citation
“…CuO photoelectrodes were employed for separated photoelectrodes. [70] This photo-assisted FeÀ O 2 battery achieved a low charging voltage of 0.64 V and a high discharging voltage of 1.38 V at 0.1 mA cm À 2 under illumination. As presented above, the photo-assisted strategies were viable to promote performances in current metal air battery systems.…”
Section: Chemistry-a European Journalmentioning
confidence: 89%
“…As for the Fe−O 2 battery, the photo‐assisted strategies were also applicable with proper photoelectrode constructions. The ZnO‐TiO 2 and pTTh‐CuO photoelectrodes were employed for separated photoelectrodes [70] . This photo‐assisted Fe−O 2 battery achieved a low charging voltage of 0.64 V and a high discharging voltage of 1.38 V at 0.1 mA cm −2 under illumination.…”
Section: Other Photo‐assisted Metal‐air Batteriesmentioning
confidence: 99%
“…[85][86][87] To address this issue which are promising solutions to the dilemma of low photon absorption efficiencies, including narrowing the bandgap and controlling the surface morphology of materials (nanophotonic structures). [39,88,89] For instance, for wide bandgap photoelectrode materials, it is one of the most commonly used methods to enhance the optical absorptivity by doping elements into the photoelectrode to adjust the band structure of the photoelectrode. [73,79] Makldis et al reported nitrogen (N)-doped TiO 2 powder samples, which were used as photoelectrodes in DSSCs (Figure 6b).…”
Section: Enhanced Light Absorptionmentioning
confidence: 99%
“…Compared with connecting high-cost photovoltaic and battery modules, SPRBs store solar energy by driving nonspontaneous reversible redox reactions in PEC cells through photoelectrode materials. [89,163,164] And delivering energy through reverse electrochemical reactions in the same device is much more cost-effective. [165,166] In order to obtain high conversion efficiency and high durability, photoanode with suitable energy level (energy level matching) needs to be considered when designing integrated photoelectrodes to meet the requirements (light harvesting efficiency and charge separation efficiency) of different devices.…”
Section: Photoelectrode Materialsmentioning
confidence: 99%
“…To overcome this limit, heterostructure construction by coupling two different functional moieties through interfacial engineering has been proposed as an effective strategy. [21][22][23] In this vein, a diversity of heterostructures comprising NiS 2 /ZnIn 2 S 4 , TiO 2 -Fe 2 O 3 , and NiCo 2 S 4 @NiO etc. have been introduced and shown to work well in catalyzing the reversible formation/decomposition of Li 2 O 2 in LiÀ O 2 batteries, improving both the Coulombic and round-trip efficiencies.…”
Section: Introductionmentioning
confidence: 99%